2019
DOI: 10.1093/jxb/erz140
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle control by the target of rapamycin signalling pathway in plants

Abstract: Cells need to ensure a sufficient nutrient and energy supply before committing to proliferate. In response to positive mitogenic signals, such as light, sugar availability and hormones, the TARGET OF RAPAMYCIN (TOR) signalling pathway promotes cell growth that connects to the entry and passage through the cell division cycle via multiple signalling mechanisms. Here, we summarise current understanding of cell cycle regulation by the RBR-E2F regulatory hub and the DREAM-like complexes, and highlight possible fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 99 publications
(129 reference statements)
0
26
0
Order By: Relevance
“…Adding to this complex network, we found that regulators of cell division and cyclin expression that are involved in developmental patterning, including the transcription factor PEAPOD2 (PPD2) ( Baekelandt et al, 2018 ; White, 2006 ) and several proteins involved in auxin signaling, which has previously been reported to act upstream of TOR ( Beltrán-Peña et al, 2002 ; Chen et al, 2018a ; Li et al, 2017b ; Schepetilnikov et al, 2017 ; Turck et al, 2004 ), are encoded by TOR-LARP1-5′TOP-regulated mRNAs. Ongoing investigations of the role of TOR in cell cycle regulation could elucidate the relative contributions of the transcriptional, translational, and post-translational regulatory steps in this multilayered TOR signaling network ( Ahmad et al, 2019 ; Lokdarshi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adding to this complex network, we found that regulators of cell division and cyclin expression that are involved in developmental patterning, including the transcription factor PEAPOD2 (PPD2) ( Baekelandt et al, 2018 ; White, 2006 ) and several proteins involved in auxin signaling, which has previously been reported to act upstream of TOR ( Beltrán-Peña et al, 2002 ; Chen et al, 2018a ; Li et al, 2017b ; Schepetilnikov et al, 2017 ; Turck et al, 2004 ), are encoded by TOR-LARP1-5′TOP-regulated mRNAs. Ongoing investigations of the role of TOR in cell cycle regulation could elucidate the relative contributions of the transcriptional, translational, and post-translational regulatory steps in this multilayered TOR signaling network ( Ahmad et al, 2019 ; Lokdarshi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because many recent reviews have summarized the status of plant TOR signaling in detail (Ahmad, Magyar, Bogre, & Papdi, 2019;Caldana, Martins, Mubeen, & Urrea-Castellanos, 2019;M. Rodriguez, Parola, Andreola, Pereyra, & Martinez-Noel, 2019;Schepetilnikov & Ryabova, 2018;Sesma, Castresana, & Castellano, 2017;Shi et al, 2018) this section will focus on effects of TOR on the translation apparatus, building on the early observation that silencing of TOR inhibits mRNA-ribosome loading (Deprost et al, 2007).…”
Section: Tor Kinase Signalingmentioning
confidence: 99%
“…Therefore, we propose that TOR translationally controls expression of cyclins to promote cell cycle progression, in addition to regulation of YAK1 upstream (Forzani et al, 2019) and E2Fa downstream of cyclin-CDK-RBR1 signaling. Ongoing investigations of the role of TOR in cell cycle regulation could elucidate the relative contributions of the transcriptional, translational, and post-translational regulatory steps in this multilayered TOR signaling network (Ahmad et al, 2019;Lokdarshi et al, 2020).…”
Section: Multilayered Regulation Of Plant Cell Cycle Progression By Tormentioning
confidence: 99%